PERBEDAAN MOTIVASI BELAJAR SISWA BERDASARKAN GENDER DALAM PEMBELAJARAN FISIKA DENGAN MODEL COLLABORATIVE LEARNING DIKELAS X MADRASAH ALIYAH AL-IHSAN BOARDING SCHOOL KAMPAR - Nurul Hasanah Hasanah; Zulhelmi '; Azizahwati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this research was to describe student’s motivation based on gender in learning physic and to describe the differences in student’s motivation based gender in learning physic by model collaborative learning in Madrasah Aliyah Al-Ihsan Boarding School. The expected benefits of this research is the basis of the increase student’s motivation to learn physics based on gender. This research was conducted in Madrasah Aliyah Al-Ihsan Boarding School, Kampar from February to May 2015. This research used 1 boy’s class with 15 students and 1 girl’s class with 18 students. Design of this research is one group pretest – posttest and data collection instrument was questionnaire. The result of this research found that boys have higher motivation then girls before treatment. Before treatment, boy’s motivation is 73,5% in high category and girl’s motivation is 69,1% in middle category. But, after being given treatment by model collaborative learning, both of class decrease learning motivation, namely 69,3% in middle category for boys and 61,1% in middle category for girls. The result show that boys have higher motivation then girls before and after given treatment Madrasah Aliyah Al-Ihsan Boarding School. Key Word :Learning Motivation, Gender, Model Collaborative Learning